Implementasi Pembelajaran Holistik Pada Mata Kuliah Hukum Islam - Kholidah Kholidah (FORUM PAEDAGOGIK, 2015)
Substantively, Islamic Law study might encourage students to practice Islamic Law in life. It is reflection of students harmony, adjustment and balance reltionship towards he or herself, other creation, nature and the creator God al mighty. The study moreover, strogly motivates students to do the practice of mahdhah and mu'amalah worships in life. In this resfect, Islamic Law study is probably performed holistic based due to:1. Society's problem-solving should be the goal of the Islamic Law study process;2. Active learning study method practice;3. Study strategy should be integrated with academic culture;4. The use of advanced media to support the study